Mediasi terhadap Kasus Penipuan Konsumen Yang dilakukan Oleh Pihak Grab: (Kasus: PT Grab Toko Indonesia di Tahun 2020) - Stefanus Edwin Ferdianto L; Dewa Gede Pradnya Yustiawan (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The purpose of this study is to find out efforts to provide legal protection to consumers who experience losses due to business actors, namely elements that are irresponsible, act recklessly and arbitrarily so that it causes harm to consumers, clearly violates and is not in accordance with applicable laws and regulations. apply and regulations. Law Number 8 of 1999 concerning Consumer Protection (UUPK) which regulates how consumer rights must be fulfilled and the obligations of corporate actors must be carried out in accordance with what has been regulated in it, applies in Indonesia and regulates customers. The perfect example of an online retailer or marketplace that operates honestly, straightforwardly and correctly is PT Grab Toko Indonesia (Grabtoko). As a business actor who has the responsibility to enforce his agreement with customers, Grabtoko does not carry out this commitment properly. It has been determined that Grabtoko is deceiving people who fall for the fake news ads it offers in its advertisements. The fraudulent activities carried out by Grabtoko have fulfilled the fraud requirements stipulated in the UUPK, including default, use of internet-based electronic media in transactions, loss of one party, and incompatibility of trading goods with representatives of the parties.